Implementation Of Philanthropy In Alleviating Poverty - Nadya Ayu Anggraeni; selfin nafilah; Hafidatuz Zuhrotunnisa' Anip (IJED: International Journal of Economy Development Research, 2025)
Philanthropy is one of the elements in religious teachings that pay attention to worldly problems, especially the problem of poverty. This study aims to explain the existing literature and present Islamic philanthropy in an effort to eradicate poverty. This research approach is qualitative content analysis with the type of literature study. This study uses secondary data such as articles, research results, and reference books. The results of the study found that research related to Islamic philanthropy in poverty alleviation from 2021 to 2022 only found 11 articles. In the instrument of Islamic philanthropy, there are pillars to support an economy, namely zakat, infaq, alms and waqf (ZISWAF). There are two main economic concepts, namely consumptive and productive. Then, it is necessary to socialize the Islamic philanthropy management scheme to the community that the management of ZISWAF is not only focused on formal worship, but can also be used for all activities that are of the common good (social worship), one of which is poverty alleviation.